Enhanced Physical-Layer Security in Visible Light Communications - A Joint Waveform Approach - Mietzner, Jan; Lampe, Lutz; Schober, Robert (2023 IEEE Photonics Conference, IPC 2023 - Proceedings, 2023)
We propose a joint waveform design for enhanced physical-layer security in visible-light communication systems using (massive) light-emitting-diode arrays suitable for sensing the presence of an illegitimate intruder and covering a large area with a jamming signal, while excluding a legitimate user.
CRIS-Team Scopus Importer:2024-12-16
Keywords: jamming; physical-layer security; sensing; spatial signal processing; Visible light communication; waveform design